Nonzero Discontinuous Inductor Current Mode in Certain Z-Source Converters - Chauhan A.K.; Raghuram M.; Singh S.K. (My University, 2025)
The continuous current mode (CCM) and discontinuous current mode (DCM) are common inductor current phenomenon seen in various Z-source converters. The CCM is characterized by nonzero rising or falling inductor current while inductor current acquires zero value during DCM. Primarily, DCM occurs in case of low inductor or light load condition. This results in difficult control of the converter due to aberrant voltage at dc terminal. However, in certain dc-ac Z-source converters, the inductor current acquires the profile of an ac load current or become constant in nature. This constant nature of inductor current occurs in case of low duty cycle condition. Constant nature in the current creates similar difficulty in control as DCM. Furthermore, it deteriorates the performance of the converter in terms of total harmonic distortion, high dc voltage ripple, increased dc voltage, and reduced peak ac voltage. This letter explains the nonzero discontinuous inductor current mode, in which constant current phenomenon appears, existence condition and case study along with performance parameters analysis. © 1986-2012 IEEE.